Synthesis of NPN-coordinated tantalum alkyl complexes and their hydrogenolysis: isolation of a terminal tantalum hydride incorporating a doubly cyclometalated NPN scaffold - Batke, Sonja; Sietzen, Malte; Wadepohl, Hubert; Ballmann, Joachim (Inorganic chemistry, 2017)
The closely related benzylene-linked diaminophosphines PhP(CH2C6H4-o-NHPh)2 (AH2) and PhP(C6H4-o-CH2NHXyl)2 (BH2 with Xyl = 3,5-Me2C6H3) were employed for the synthesis of tantalum(V) alkyls, which were then studied with respect to hydrogenolysis. In the case of AH2, the tantalum trimethyl complex [Ta(A)Me3] (1) and the tantalum hydrocarbyl complex [Ta(A)(CH2SiMe3)(η2-EtC≡CEt)] (2) were prepared from the ligand’s dilithium salt (A)Li2(diox). Upon hydrogenolysis of 1 and 2, the formation of methane and SiMe4, respectively, was observed, but well-defined tantalum hydrides could not be detected. In the case of BH2, the cyclometalated species [Ta(B*)(NMe2)2] (3 with B* = κ4-N,P,N,C-(PhP(C6H4-o-CH2NXyl)(C6H4-o-CHNXyl))3-) was isolated and converted to the corresponding diiodo species [Ta(B*)I2] (4). Treatment of 4 with LiCH2SiMe3 resulted in the isolation of the corresponding dialkyl complex [Ta(B*)(CH2SiMe3)2] (5), which was converted to the doubly cyclometalated monoalkyl complexes [Ta(B**)(CH2SiMe3)(PMe3)] (6 with B** = κ5-C,N,P,N,C-(PhP(C6H4-o-CHNXyl)2)4-) and [Ta(B**)(CH2SiMe3)(dmpe)] (7) via reaction with PMe3 and dmpe, respectively. In contrast to 5 and 6, 7 was found to react cleanly with dihydrogen to afford the corresponding terminal tantalum(V) hydride [Ta(B**)(H)(dmpe)] (8). Upon reaction of 7 with D2, the deuteride [Ta(d2-B**)(D)(dmpe)] (9) was obtained and found to contain deuterium atoms in the methine positions of both tantalaaziridine subunits. The partially deuterated derivatives [Ta(B**)(D)(dmpe)] (10) and [Ta(d2-B**)(H)(dmpe)] (11) were generated via reaction of 8 and 9 with PhSiD3 and PhSiH3, respectively. Prior to the addition of gaseous D2 or H2, no H/D scrambling was observed in 10 or 11, indicating that the exchange of the methine positions proceeds via addition of D2 or H2 across the tantalaaziridine Ta-C bonds.